How to Do Everything with Online Video - Shalat, Andrew (New York McGraw-Hill, 2007)
A guide to planning, creating, editing, and sharing video content online. This title shows how to shoot professional-quality videos, edit the files, prepare clips for posting online, and share video projects through a variety of websites, blogs, and podcasts. It includes hands-on tutorials for video editing software for use on PCs and Macs.
Include Illustrations and Index
Keywords: Internet videos